Current Trends and Future Prospects in Global Production, Utilization, and Trade of Pearl Millet - Deevi, Kumara Charyulu; Swamikannu, Nedumaran; Gumma, Murali Krishna; Pingali, Parthasarathy Rao (Springer, 2024)
Millets are a group of small-seeded annual grasses that occupy the sixth position after rice, wheat, maize, barley, and sorghum globally. Among the millets, pearl millet (Pennisetum glaucum R. Br.) represents approximately 75% of the global millet area. Around 70% of total millet is produced under warm tropics dryland climates with Africa and Asia accounting for 98% of the global area and 97% of global production. Among the countries, India is the largest producer followed by China, Niger, and Nigeria. The area under millets has come down globally from 35 to 32 million ha between 2007 and 2019 mainly due to the decline in Asia. Yields, however, increased significantly in Asia from 1100 kg/ha to 1292 kg/ha while it declined marginally in Africa. Globally, nearly 3/4 of the domestic supply of millet is used for food, and the rest is used for feed and other uses. Developed countries mainly use millet for animal feed/bird feed. The nutritive and gluten-free nature of millet has provided ample scope across the globe for developing several nutrition-based products, beverages, and baby foods. The enhanced demand for processed foods augers well for millet though still in a nascent stage. Millets are thinly traded with less than 2% of total millet production being exported. Despite this based on International Food Policy Research Institute’s (IFPRI’s) IMPACT (International Model for Policy analysis of Agricultural Commodities and Trade) model projections, global millet demand is set to increase from 48.5 to 66.5 million tons between 2030 and 2050, and in Asia projected supply would be lower than the demand indicating a widening gap with scope for enhanced trade to meet the shortfall. Since millets are grown under poor soil and marginal environmental conditions, their yields are unstable due to biotic and abiotic stresses besides socio-economic constraints like linkage to markets, access to credit, etc. Addressing these constraints would enhance not only the competitiveness of millets but also the scope for expanding to more favorable areas.